Émotions manipulées ː l’affaire DSK vue par les news magazines français - Kacprzak, Alicja; Goudailler, Jean-Pierre (Studia Romanica Posnaniensia, 2015)
Taking as a starting point the nowadays evident role of media in the process of forming public opinion, our article focuses on the function performed in it by the title pages of periodicals. The analysis of their iconic and textual message (based on the covers of French magazines concerning the so-called affaire DSK) allows to state that it mainly serves the purpose of building up emotions in the receiver, which eventually is meant to achieve a certain persuasive effect